2017
DOI: 10.1111/jdi.12779
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between deterioration of glycated hemoglobin‐lowering effects in dipeptidyl peptidase‐4 inhibitor monotherapy and dietary habits: Retrospective analysis of Japanese individuals with type 2 diabetes

Abstract: The present study was designed to assess possible relationships between deterioration of the glycated hemoglobin (HbA1c)‐lowering effects in dipeptidyl peptidase‐4 inhibitor (DPP4i) monotherapy and macronutrient intake among individuals with type 2 diabetes. Type 2 diabetes patients who began and continued DPP4i monotherapy without any prescription change for 1 year were retrospectively stratified into two groups: (i) patients who maintained their HbA1c levels during the 0.5‐ to 1‐year period after DPP4i initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Finally, our study could not differentiate the effects of different fats on the response of the gut–incretin axis, since the fat emulsion contained a mixture of saturated and unsaturated dietary fat. Given potential differences in the incretin response to saturated and unsaturated fat, and that dietary intake of saturated fat may be associated with a deterioration in glycaemic control during DPP‐4 inhibitor monotherapy in T2DM, studies to evaluate the influence of the type of fat on metabolic outcomes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study could not differentiate the effects of different fats on the response of the gut–incretin axis, since the fat emulsion contained a mixture of saturated and unsaturated dietary fat. Given potential differences in the incretin response to saturated and unsaturated fat, and that dietary intake of saturated fat may be associated with a deterioration in glycaemic control during DPP‐4 inhibitor monotherapy in T2DM, studies to evaluate the influence of the type of fat on metabolic outcomes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In Japanese patients with T2DM treated with a DPP‐4 inhibitor as monotherapy for 1 year, fat intake, especially saturated fat was shown to be significantly associated with deterioration of HbA1c levels (≥0.4%) …”
Section: Idepmentioning
confidence: 99%
“…104 In Japanese patients with T2DM treated with a DPP-4 inhibitor as monotherapy for 1 year, fat intake, especially saturated fat was shown to be significantly associated with deterioration of HbA1c levels (≥0.4%). 105 There is little evidence regarding exercise and pharmacotherapy interaction. In contrast to the findings demonstrating exercise improves glycaemic and metabolic parameters in patients with T2DM, one study demonstrated that aerobic exercise did not acutely increase total GLP-1 and GIP levels in patients with T2DM, however, metformin treatment, independent of exercise, significantly increased total plasma GLP-1 and GIP concentrations.…”
Section: Idepmentioning
confidence: 99%
“…The effects of MNT on the efficacy and safety of glucose‐lowering agents, such as DPP‐4 inhibitors and sodium–glucose cotransporter 2 inhibitors, are an intriguing area of investigation. Recently, it has been reported that in some type 2 diabetes patients who consume more fats, but not more carbohydrates, DPP‐4 inhibitor treatment increases bodyweight, probably through enhancement of GIP secretion and action, and its glucose‐lowering effects are impaired for several months after initiation of DPP‐4 inhibitor treatment. In animal experiments, both wild‐type mice fed a high‐fat diet and high‐starch diet show obesity and enhanced glucose‐induced insulin secretion.…”
mentioning
confidence: 99%
“…The effects of MNT on the efficacy and safety of glucose-lowering agents, such as DPP-4 inhibitors and sodiumglucose cotransporter 2 inhibitors, are an intriguing area of investigation 8,14 .…”
mentioning
confidence: 99%